Structural multiplicity in a solvated hydrate of the antiretroviral protease inhibitor Lopinavir - Tebogo M. L. Mokoto; Andreas Lemmerer; Yasien Sayed; Mark G. Smith (Acta Crystallographica Section E: Crystallographic Communications)
Lopinavir is a potent protease inhibitor that is used as a first-line pharmaceutical drug for the treatment of HIV. The multi-component solvated Lopinavir crystal, systematic name (2S)-N-[(2S,4S,5S)-5-[2-(2,6-dimethylphenoxy)acetamido]-4-hydroxy-1,6-diphenylhexan-2-yl]-3-methyl-2-(2-oxo-1,3-diazinan-1-yl)butanamide–ethane-1,2-diol–water (8/3/7) 8C37H48N4O5·3C2H6O2·7H2O, was prepared using evaporative methods. The crystalline material obtained from this experimental synthesis was characterized and elucidated by single-crystal X-ray diffraction (SC-XRD). The crystal structure is unusual in that the unit cell contains 18 molecules. The stoichiometric ratio of this crystal is eight Lopinavir molecules [8(C37H48N4O5)], three ethane-1,2-diol molecules [3(C2H6O2)] and seven water molecules [7(H2O)]. The crystal packing features both bi- and trifurcated hydrogen bonds between atoms.